An Efficient Resource and Topological Attribute-Based Configuration Algorithm of Virtual Networks. (28th September 2021) - Wang, Xinyan; Li, Shunbin; Bai, Longju
Abstract : In the future Internet operation and service model, users put forward network application requirements, and the service provider allocates the corresponding virtual network for users according to the demands. Virtual network resource allocation is an NP-hard problem; hence, the existing research work is mainly based on heuristic algorithms to solve the above problem. However, these traditional algorithms based solely on resource attributes are not sufficient to configure virtual networks. We design a virtual network configuration algorithm (ERTA-CA) based on the two-stage heuristic resource utilization that considers both local and global resource attributes and topological attributes of the network. The experimental results verify that our proposed algorithm can improve the acceptance rate and configuration revenue of the virtual network, which further indicates that ERTA-CA can achieve the virtual network configuration with efficient use of resources.